The regulation of pharmacy ownership in Australia: the potential impact of changes to the health landscape - Hattingh, H. Laetitia (Thomson, 2011)
Australian community pharmacy ownership restrictions have been in place for many years. However, it is timely to review these structures in terms of the Commonwealth Government’s proposed changes to the health care system and the need for flexibility to ensure access of vital medicines to the community. Careful consideration has to be given to the advantages and disadvantages of regulatory structures that limit ownership to pharmacists, compared to non-pharmacist ownership. Other ownership aspects that need to be evaluated include the number of pharmacies one pharmacist should be allowed to own or co-own and the extent of control required on the location of pharmacies.